Catalytic Interfaces‐Enriched Hybrid Hollow Spheres Sulfur Host for Advanced Li–S Batteries. Issue 1 (22nd November 2019) - Yang, Jin‐Lin; Zhao, Shi‐Xi; Zeng, Xiang‐Tian; Lu, Yi‐Ming; Cao, Guo‐zhong
Abstract: Lithium–sulfur (Li–S) batteries are considered as a promising next‐generation energy storage technology due to its high energy density over 2500 Wh kg −1 and low cost. Its development and application require to overcome several obstacles including the large volume change, the low electrical conductivity of S/Li2 S, and the shuttle effect of lithium polysulfides (LIPSs). In this work, the hollow N‐doped carbon spheres (NHCS) decorated with nanosized SnS2 (NHCS‐SnS2 ) are synthesized and investigated to host sulfur used as the cathode for Li–S batteries. Highly conductive NHCS offer a large specific surface area and robust confinement for active material S, while SnS2 nanoparticles provide efficient chemisorption of LIPSs and promote the deposition of solid Li2 S. The NHCS‐SnS2 /S cathode materials deliver a high discharge capacity 1344 mAh g −1 at 0.2 C and a low capacity decay over 200 cycles at 0.5 C. The outstanding cycling stability at 0.2 C with high sulfur loading of 3.0–3.1 mg cm −2 can also be readily attained. The excellent electrochemical performance is attributed to possible triple phase catalytic effect of NHCS‐SnS2 and electrolyte, and such structure permits the full utilization of active materials from S8 to Li2 S. Abstract : Catalytic interfaces enriched sulfur host is synthesized by facile hydrolysis and sulfurization process to decorate the hollow N‐doped carbon spheres (NHCS) with well‐dispersed nanosized SnS2 . Coupled with electrolyte, such hybrid structure can offer a fast lithium polysulfides conversion kinetics with the aid of carbon‐SnS2 ‐electrolyte triple phase interface. In this work, the NHCS‐SnS2 /S cathode delivers outstanding rate performance and capacity retention.